Acute Glycemic Variability and Functional Outcome in Patients with Acute Ischemic Stroke: A Meta-Analysis - Lin, Jinbo; Cai, Chunsheng; Xie, Yituan (Hormone and Metabolic Research, 2022)
Dysglycemia are involved in the development of functional impairment after acute ischemic stroke (AIS). The aim of the study was to evaluate the association between acute glycemic variability and functional outcome in patients with AIS. Cohort studies were obtained by search Medline, Web of Science, Embase, Wanfang, and China National Knowledge Infrastructure databases from inception to November, 2021. A random-effect model which incorporates the intra-study heterogeneity was chosen to pool the results. Ten cohort studies including 3038 patients were included, and 1319 (43.4%) had poor functional outcome (modified Rankin Scale >2) up to three months after disease onset. Pooled results showed that higher acute GV was associated with an increased risk of poor functional outcome, as evidenced by GV evaluated by the standard deviation of blood glucose (SDBG, OR: 1.91, 95% CI: 1.38 to 2.65, I2=60%, p<0.001), the coefficient of variation of blood glucose (OR: 2.03, 95% CI: 1.15 to 3.58, I2=17%, p=0.02), the range of glucose (OR: 1.43, 95% CI: 1.11 to 1.83, I2=22%, p=0.005), and the mean amplitude of glycemic excursion (OR: 1.59, 95% CI: 1.10 to 2.31, I2=0%, p=0.01). Subgroup analyses did not support that difference in study design, treatments for AIS, mean age of the patients, duration for GV measuring, or study quality would significantly affect the association between SDBG and functional outcome after AIS. In conclusion, higher acute glycemic variability may predict poor functional outcome within 3 months after AIS.
Keywords: glycemic variability; acute ischemic stroke; functional dependence; modified Rankin Scale; meta-analysis